Islamic Economic and Financial Practices in Indonesia: From Local to a Potential Global Framework - Azharsyah Ibrahim (Share: Jurnal Ekonomi dan Keuangan Islam, 2023)
This issue continues to showcase the distinctiveness of Islamic economic and financial practices in Indonesia and their potential relevance globally. It covers various aspects, including emerging trends in Islamic economics research, the significance of Islamic economics and finance in the modern economy, institutional performance, financial stability, waqf institutions, and the societal role of Islamic economics and finance. The selection process for the articles followed several rigorous steps. Upon receiving each submission, an initial check was conducted to assess its suitability with the journal's aim and scope. Subsequently, the manuscripts were sent to two appropriate reviewers for a double-blind peer review process. In some cases, manuscripts required multiple rounds of evaluation before final acceptance. The feedback provided by the reviewers played a crucial role in making the final decisions. Upon acceptance, the manuscripts proceeded to the editing stages, where they underwent meticulous proofreading and layout design. Throughout this stage, close and constant communication between our editors and the respective authors was maintained to ensure the clarity and coherence of the final articles. From the numerous submissions received, only 12 outstanding papers were selected for publication. Each of these articles offers valuable contributions to the field of Islamic economics and finance, and they have been carefully chosen for their originality, relevance, and potential impact on the scholarly community. We believe that these selected papers will enrich the understanding and discourse surrounding Islamic economics and finance, both in Indonesia and beyond.